The Role Of Character In The Development Of Leadership Skills Of Students - Albina Anesova, Nazgul Кudarova, Gulmira Tulekova, Saltanat Aubakirova, (Opción, 2019)
The aim of the study is to investigate the role of national character in the development of leadership skills of university students via comparative qualitative research methods. As a result, the level of national spirit and patriotism were prevailed at the students studying on educational specialties, than students of technical specialties. Proceeding from results of the stating experiment, we developed the author’s methodology of development of leadership skills at the future specialists. Thus, the conducted stating experiment confirmed need of the research of national character, and identification of its influence on development of leadership skills at students in the university.